Moral panics on lgbt issues: evidence from indonesian tv programme - Listiorini, Dina; Asteria, Donna; Sarwono, Billy (Faculty of Communications Science, Dr. Soetomo University, 2019)
There was a discussion activity conducted by a small club of the University of Indonesia called SGRC (Support Group and Resource Center on Sexuality Studies) at the beginning of January 2016. It did not only discuss sexuality such as sexual preferences but also conduct peer support for LGBT groups. However, it was reported illegal for many reasons. Although later the â€œillegalâ€ stamp was dubbed as an